Pre-distribution asymmetric key management scheme for mobile ad hoc networks - Lei HAN; Ji-qiang LIU; Zhen HAN; Xue-ye WEI (Tongxin xuebao)
In order to reduce communication overhead of the asymmetric key management in mobile ad hoc networks,an identity-based pre-distribution asymmetric key management scheme(PAKMS)was presented based on combined public key(CPK)framework,ElGamal public key cryptosystem and key pre-distribution mode.This scheme essentially reduced communication overhead of the asymmetric key management in mobile ad hoc networks by the private key generation (PKG)distributing a subset of master key for every node beforehand and a time-based key update approach.The method that PKG pre-distributed a subset of master key also made the nodes obtain their keys and key update services,which did not need to rely on online PKG.Thus,the inherent key escrow problem existing in identity-based asymmetric key management was avoided to some degree.Compared with typical schemes,this scheme needed much less communication overhead to accomplish node key update service.Furthermore,security proof of the scheme was described in detail.